Study Lanskap Linguistik pada Penamaan Tempat Ibadah (A Linguistic Landscape Study of the Naming of Places of Worship) - Qulub, Muhammad Farihul; Rusmawati, Roosi; Ardhian, Dany; Hamidi, Saddam Reza (Universitas Sebelas Maret, 2026)
This study aims to investigate the linguistic landscape on the naming of places of worship that can be observed in the religious and cultural and social landscapes. Some languages are also found on common signs in places of worship. The problem focuses on the function of information and symbols to find the landscape motif that occurs in the naming of the worship theme. This study uses Linguistic Landscape Theory, which describes the existence of linguals, linguistic ideologies, and lingual competition. The research method uses a phenomenological approach with a qualitative descriptive research type, although some information uses numerical data. The target of the study is language identity in Lamongan with the most popular language pattern instruments, namely Indonesian, Arabic, Javanese, Sanskrit. The results of the study show that the linguistic landscape in the naming of places of worship has several information functions (1) as a manifestation of the identity of places of worship, (2) as information on the owners of places of worship, (3) as a means of informing religious streams, sects, and mass organizations, (4) as a means of promotion, (5) as a location marker. While the symbolic function shows (1) the symbolic function of the Indonesian language as the essence of the harmony of religious organizations, (2) the symbolic function of the Arabic language as modernity and identity, (3) the symbolic function of the Javanese language: traditionality and historical preservation.